Simulation of stress concentration factors in combined discontinuities on flat plates. (August 2016) - Santos, A; Guzman, R; Ramirez, Z; Cardenas, C
Abstract: The objective of this paper was to determine the stress concentration factors for static load conditions (Kc) through the use of a finite elements software. The concentrators originate an increase in the calculated stress to design mechanical elements so that quantify this increase allow to obtain viable designs capable to endure the loads to which they are subjected. Among the most relevant results is validation, through statistical analysis, of use of ANSYS software for the determination of this parameter in flat plates with a central hole subjected to axial load conditions; the graphs of Kc for flat plates with combined discontinuities, central hole - groove and central hole - fillet, under axial load conditions were also obtained; the Kc value for flat plates with central hole - groove has a polynomial relation of degree 5 with the r/h parameter and decreases in so far as that this magnitude increases; additionally is also demonstrated that the concentration factor depends on the H/h relation and there is no defined trend between these two parameters. The Kc value for flat plates with central hole - fillet has a polynomial relation of degree 5 with the r/h parameter and also depends on the relation H/h without showing a defined trend between these two parameters.